A Mass Spectrometric Study of Kratom Compounds by Direct Infusion Electrospray Ionization Triple Quadrupole Mass Spectrometry - Fu, Hanzhuo (Scientific Research Publishing, 2016)
Mitragynine (MG) and its major metabolites 7-hydroxymitragynine (7-OH-MG) are two of the major components of the plant extract Kratom, which is a tree planted in Southeast Asia. Kratom has long been used by opioid-dependent individuals as an alternative to their unavailable opioid of choice and chronic pain medication, as a stealth-to-urine drug screening opiate substitute while in opioid recovery treatment and recreationally, alone or as a booster. In this study, a direct infusion method was utilized and electrospray ionization triple quadrupole mass spectrometer was used as the detector for data acquisition. Pharmacokinetic study was conducted to investigate the effect of mitragynine and 7-hydroxymitragynine and major fragments of both compounds were proposed.
A Mass Spectrometric Study of Kratom Compounds by Direct Infusion Electrospray Ionization Triple Quadrupole Mass Spectrometry
Keywords: Mitragynine; 7-Hydroxymitragynine; Kratom; HPLC-MS/MS; Pharmacokinetic; Mass Fragment